ROLL UP / VENEZ: AN INVITATION TO CORPUS-BASED RESEARCH IN MOTION TYPOLOGY - Cappelle, Bert (Programa de Pós-Graduação em Letras Vernáculas da Faculdade de Letras, 2021)
This paper highlights some facets of motion typology, applied here to mainly English and French. These two languages are not perfect examples of satellite-framed and verb-framed languages, in Leonard Talmy’s well-known typology, but they can nonetheless be shown to differ in a number of related respects: compared to English (and other Germanic languages), French (like other Romance languages) is quite constrained in its use of Manner-of-motion verbs. French also lacks true particles – Path satellites without a Ground that can be syntactically detached from the verb. Drawing on some of my previous research, I briefly discuss two simple but apparently sufficiently efficient corpus-based translation studies that reveal that these differences show up when we compare English texts originally written in English with English texts translated from French vs. English texts translated from German (or other Germanic languages). A third, more recent, study contrasts a single English novel with its French and Dutch translations, focusing on expressions of visual motion. Here, too, some of the basic encoding preferences (satellite-framed vs. verb-framed) that these languages exhibit for actual motion appear to apply, by and large, for visual motion. This paper also lists some precursors of Talmy, one of whom is famously linked with the linguistic relative hypothesis. It is suggested that French, because of its typological nature, may not urge its speakers to convey much detail (neither of Manner nor of Path) in the encoding of motion. It remains an open question, one that goes beyond the purview of corpus linguistics, whether this stylistic difference is matched with a deeper cognitive one.